Effect of Zn2+ ions on structural, optical, magnetic, and impedance response of Znx@Ni1–xFe2O4 core materials prepared by two‑step polyacrylamide gel method - Sankaranarayanan, R.; Shailajha, S.; M. S., Kairon Mubina; C. P., Anilkumar (My University, 2020)
Spinel ferrite nanocomposites of Znx@Ni1–xFe2O4 (x=0, 0.2, 0.4, 0.6, and 0.8) system were developed by two-step polyacrylamide sol–gel method. The two phases (Fd-3m and P63mc) of the nanocomposites were confirmed by applying XRD results using the Rietveld refinement program. The addition of ‘Zn’ content causes the occupations of Zn2+ ions over the tetrahedral and octahedral sites of Ni2+/Fe3+ ions were analyzed by XPS spectra. The broad absorbance and band gap values of the samples were obtained by UV-DRS. The morphology and elemental percentage of the nanocomposites were determined by using FESEM and EDS spectrum. In VSM and impedance analysis, the enhanced ferromagnetic and the impedance behavior of material was analyzed and the saturation magnetization enhanced from 32 to 54 emu/g until x=0.4, then decreased to 28 emu/g. The permeability has enhanced as 8.76% and the impedance value with and without magnetic field attains maximum at x=0.4.
Keywords: Zn2+ ions; Znx@Ni1–xFe2O4 core materials; Polyacrylamide gel method